2015
DOI: 10.1097/sla.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal/Transumbilical Hybrid—NOTES—Versus 3-Trocar Needlescopic Cholecystectomy

Abstract: In a randomized clinical trial, needlescopic 3-trocar cholecystectomy was compared with transvaginal/transumbilical hybrid—NOTES—technique for symptomatic cholecystolithiasis. We found significantly less pain despite less analgesics, increased satisfaction with the aesthetic result, and improved postoperative quality of life in the NOTES group. Furthermore, both techniques were equal in terms of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…The risk of bias in included RCTs, according to the Cochrane Collaboration risk‐of‐bias tool, was unclear for random sequence generation but low for all other domains. Several trials did not report how many patients were screened for inclusion in the trial, how many declined to participate, and how many possibly eligible patients were not asked to participate. There is therefore an unclear risk of selection bias due to inadequate generation of a randomized sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias in included RCTs, according to the Cochrane Collaboration risk‐of‐bias tool, was unclear for random sequence generation but low for all other domains. Several trials did not report how many patients were screened for inclusion in the trial, how many declined to participate, and how many possibly eligible patients were not asked to participate. There is therefore an unclear risk of selection bias due to inadequate generation of a randomized sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Six RCTs and 15 non‐randomized trials reported on postoperative pain on day 1 using a numerical rating scale (NRS) (0, no pain; 10, strongest pain). In a random‐effects model, the NRS score for hybrid NOTES was lower than for standard laparoscopy (MD −0·75, 95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
“…19 Outcomes have been similar to those achieved with laparoscopic cholecystectomy, although it is associated with a better aesthetic outcome, a shorter recovery time, and less pain. 21,22 Overall sexual function does not appear to be adversely affected, 23 and there have been no reports of the development of fistulae or fertility problems after transvaginal cholecystectomy. NOTES requires special equipment and is technically very difficult.…”
Section: Notesmentioning
confidence: 99%
“…This technique is associated with longer operative time than CLC, and the conversion rate of TVC to CLC is estimated at 10% [47] . To date, three randomized control trials have been published, comparing transvaginal hybrid cholecystectomy to conventional [47,48] or needlescopic [49] laparoscopic cholecystectomy, along with one metaanalysis [50] . The proponents of NOTES cite reduced postoperative pain as an advantage of TVC over CLC.…”
Section: Natural Orifice Transluminal Endoscopic Cholecystectomymentioning
confidence: 99%